UNIVERSALITAS EKONOMI SYARIAH (PENDEKATAN DIALOG AGAMA) - elysa najachah (UIN Walisongo Semarang, 2020)
Economy is an inseparable thing in life. For that we need dialogue skills in various aspects of life related to the economy. The religious dialogue approach is an alternative to solving economic problems. This study uses an interfaith study approach. Islamic economics emerged with rules prohibiting all forms of usury. The prohibition of usury has been put forward by other religions. Religious dialogue regarding the economic view of Sharia has been carried out. The findings of this study are that there is a side of universality obtained from Islamic economics as a solution to economic problems that can be accepted by Islam and non-Islamic religions.